Characteristics related to higher rubber yield of Hevea brasiliensis juvenile-type clone Gl 1 - Yuan Xie-Hui; Hao Bing-Zong; Wu Ji-Lin; Xu Lai-Yu; Yang Shang-Qiong (Journal of Rubber Research, 1998)
In a comparative trial between G11 juvenile-type buddings (JT buddings) and mature-type buddings (MT buddings), the structural and physiological characteristics of the JT buddings tapped for about 5 years were studied in relation to their higher yield performance. The JT buddings were derived from the juvenile buds of 1.5 year old anther somatic plants produced by tissue culture and MT buddings from normal planting materials. The dry rubber yield in g/tree/tapping during the first 4 years was 25;-40;higher in the JT buddings than in the MT buddings. In comparison with the MT buddings, the JT buddings had increased girth and bark thickness, larger total number of laticifer rings, higher dry rubber content, higher mean initial rate of latex flow, lower plugging index and lutoid bursting index, higher latex sucrose and inorganic phosphorus contents, and a similar level of latex thiol content. Based on these results and data available, it is inferred that the juvenile-type clones are superior to the corresponding mature-type clones both in the latex flow and in latex regeneration and they may be promising planting materials in future rubber production.